Non-invasive vagus nerve stimulation for treatment of cluster headache: a retrospective review of prescribing in England. Issue 11 (2nd November 2021) - Silver, Nicholas; Bradley, Carl; Stuckey, Rebecca; Murphy, Madeleine; Greenwood, Fiona; Abdallah, Angela; Weatherby, Stuart; Lambru, Giorgio; Ahmed, Fayyaz; Liebler, Eric; Edey, Paul; Strickland, Iain; et al.
Abstract : Background/Aims: Beginning in April 2019, non-invasive vagus nerve stimulation was included in the NHS Innovation and Technology Payment programme. The programme guaranteed reimbursement of at least a 3-month course of treatment using gammaCore, through a prescription refill card, authorised by a headache specialist for patients with cluster headache who reported a clinically meaningful benefit. This study evaluated prescribing and refill trends to assess the use of gammaCore in England since the beginning of this programme. Methods: Data regarding gammaCore prescriptions and refills from 1 April 2019 to 31 December 2020 were collected and tabulated. Patients were categorised into three groups: those who initiated gammaCore therapy under the programme (new starters), those who were prescribed ≥1 refill, and those who were prescribed ≥2 refills. One refill corresponds to 3 months of gammaCore therapy. Results: In total, 52 NHS sites submitted 2092 prescriptions for gammaCore devices, including 655 for new starters. Among new starters, 46.3% received ≥1 refill and 30.9% received ≥2 refills. Those who started using gammaCore after its inclusion in the Innovation and Technology Payment programme received up to seven refills during the data collection period, representing 21 months of therapy. Conclusions: This is one of the largest clinical audits of patients with cluster headache. Patients' continued use of gammaCore treatment through multiple 3-month refills in this audit suggests that non-invasive vagus nerve stimulation is efficacious, tolerable and practical for patients with cluster headache.